Interactions of arctic clouds, radiation, and sea ice in present-day and future climates - Burt, Melissa Ann, author; Randall, David A., advisor; Kreidenweis, Sonia M., committee member; Kummerow, Christian D., committee member; Betsill, Michele M., committee member (Colorado State University. Libraries, 2016)
The Arctic climate system involves complex interactions among the atmosphere, land surface, and the sea-ice-covered Arctic Ocean. Observed changes in the Arctic have emerged and projected climate trends are of significant concern. Surface warming over the last few decades is nearly double that of the entire Earth. Reduced sea-ice extent and volume, changes to ecosystems, and melting permafrost are some examples of noticeable changes in the region. This work is aimed at improving our understanding of how Arctic clouds interact with, and influence, the surface budget, how clouds influence the distribution of sea ice, and the role of downwelling longwave radiation (DLR) in climate change. In the first half of this study, we explore the roles of sea-ice thickness and downwelling longwave radiation in Arctic amplification. As the Arctic sea ice thins and ultimately disappears in a warming climate, its insulating power decreases. This causes the surface air temperature to approach the temperature of the relatively warm ocean water below the ice. The resulting increases in air temperature, water vapor and cloudiness lead to an increase in the surface downwelling longwave radiation, which enables a further thinning of the ice. This positive ice-insulation feedback operates mainly in the autumn and winter. A climate-change simulation with the Community Earth System Model shows that, averaged over the year, the increase in Arctic DLR is three times stronger than the increase in Arctic absorbed solar radiation at the surface. The warming of the surface air over the Arctic Ocean during fall and winter creates a strong thermal contrast with the colder surrounding continents. Sea-level pressure falls over the Arctic Ocean and the high-latitude circulation reorganizes into a shallow "winter monsoon." The resulting increase in surface wind speed promotes stronger surface evaporation and higher humidity over portions of the Arctic Ocean, thus reinforcing the ice-insulation feedback. In the second half of this study, we explore the effects of super-parameterization on the Arctic climate by evaluating a number of key atmospheric characteristics that strongly influence the regional and global climate. One aspect in particular that we examine is the occurrence of Arctic weather states. Observations show that during winter the Arctic exhibits two preferred and persistent states — a radiatively clear and an opaquely cloudy state. These distinct regimes are influenced by the phase of the clouds and affect the surface radiative fluxes. We explore the radiative and microphysical effects of these Arctic clouds and the influence on these regimes in two present-day climate simulations. We compare simulations performed with the Community Earth System Model, and its super-parameterized counterpart (SP-CESM). We find that the SP-CESM is able to better reproduce both of the preferred winter states, compared to CESM, and has an overall more realistic representation of the Arctic climate.